Using web-site QEM to measure the quality of sites - Olsina Santos, Luis Antonio (2000)
In this position paper, the main steps to measure and evaluate quantitatively the quality of sites are shown. Besides, some specific models, criteria and procedures to apply in these activities are discussed by quoting case studies already performed (e.g., in the academic domain [4] as well as in museums [3] and e-commerce domain [6]). In order to get a general insight, we focus on the overview oí the proposed methodology called Web-site Quality Evaluation Method '(QEM). The proposed stepwise, expert-driven, model-based methodology is essentially quantitative, flexible, and robust covering most of the activities in the evaluation, comparison, and ranking process oí websites.